Respuesta :

for [tex]f(x)=ax^n+bx^{n-1}...+z[/tex] where n is the highest power of the function
if n is even and 'a' is positive, the graph goes from top left to top right
if n is even and 'a' is negative, the graph goes from bottom left to bottom right      
if n is odd and 'a' is positive, the graph goes from bottom left to top right           
if n is odd and 'a' is negative, the graph goes from top left to bottom right


and, for [tex]f(x)=a(x-r_1)(x-r_2)(x-r_3)...(x-r_n)[/tex], it intersects the graph at [tex]x=r_1[/tex], [tex]x=r_2[/tex],[tex]x=r_3[/tex], up to [tex]x=r_n[/tex],

so see what we've got[tex]f(x)=-x^3-x^2+4x+4[/tex]            
factor and group              
[tex]-x^3-x^2+4x+4=(-x^3-x^2)+(4x+4)=[/tex]                 [tex](-x^2)(x+1)+(4)(x+1)=(x+1)(4-x^2)=(x+1)(2-x)(2+x)=[/tex]                [tex]-1(x+2)(x+1)(x-2)[/tex]                     [tex]f(x)=-1(x-(-2))(x-(-1))(x-2)[/tex]                a=-1               the roots are x=-2, x=-1, x=2                since n=3 (from [tex] -x^3-x^2+4x+4[/tex]) and a is negative, we know it goes from top left to bottom right             also, it intersects at x=-2,-1, and 2

answer is the 3rd option: It starts up on the left and goes down on the right and intersects the x-axis at x = −2, −1, and 2.
ACCESS MORE